The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/jbim-09-2021-0414
|View full text |Cite
|
Sign up to set email alerts
|

A review of coopetition and future research agenda

Abstract: Purpose This research aims to conduct a systematic review of the literature on coopetition to assess its impact on firm performance in various contexts. Design/methodology/approach A bibliometric analysis of 144 papers from 1999 to 2021 and analysis of literature under the premise of theory, context, characteristics and methodology using the Theory–Context–Characteristics–Methodology (TCCM) approach was conducted using Institute for Scientific Information Web of Sciences data on coopetition literature. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 155 publications
0
16
0
Order By: Relevance
“…From a methodological perspective, our research contributes to the strand of literature that examines coopetition from a game-theoretic perspective (Chen et al , 2019; Meena et al , 2022). Our theoretical analysis uncovers several interesting mechanisms and interactions that improve our understanding of the necessary balance between collaboration and competition in successful coopetitive activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a methodological perspective, our research contributes to the strand of literature that examines coopetition from a game-theoretic perspective (Chen et al , 2019; Meena et al , 2022). Our theoretical analysis uncovers several interesting mechanisms and interactions that improve our understanding of the necessary balance between collaboration and competition in successful coopetitive activities.…”
Section: Discussionmentioning
confidence: 99%
“…We show that privately informed firms with superior absorptive capacities are more likely to offer alliances for the main purpose of accessing and exploiting the internal capabilities of the competitor rather than capitalising on the business opportunity that gives rise to the cooperation. These theoretical insights also allow us to shed light on the question of how smaller firms leverage coopetition while interacting with larger firms (Meena et al , 2022). We show that uninformed firms with limited absorptive capacities but highly specialised products (such that the degree of product similarities is low) are less likely to face the type of opportunistic behaviours previously described because, for these firms, even limited learning about the production process of their partners has a significant effect on the degree of competition in the product market.…”
Section: Introductionmentioning
confidence: 99%
“…In this systematic literature review, bibliometric analysis is used, followed by cluster formation using co-citation analysis. Bibliometric methods in systematic literature review assess the extant literature and remove researcher bias (Singh and Dhir, 2019;Meena et al, 2022;Zupic and Cater, 2015). This method of analysis provides insights into a large number of research articles.…”
Section: Methodsmentioning
confidence: 99%
“…Coopetition explains the "growing interorganisational cooperative relationships between competing firms" and more research is needed to further investigate it's "conceptualization and its strategic applicability, as well as its management in different settings" (Bouncken et al, 2015). A systematic literature review revealed six research themes: "coopetition leading to innovation performance," "knowledge sharing and organizational learning in coopetition," "tension and paradox as a challenge in coopetition," "the effect of coopetition on firms," "the impact of coopetition on the supply chain" and "determinants of coopetition" (Meena et al, 2022). Another systematic literature review by Bengtsson and Raza-Ullah (2016) opines that studies on coopetition can be categorised into two schools: "the Actor and the Activity Schools of Thought".…”
Section: Foundational Literaturementioning
confidence: 99%
“…, 2015). A systematic literature review revealed six research themes: “coopetition leading to innovation performance,” “knowledge sharing and organizational learning in coopetition,” “tension and paradox as a challenge in coopetition,” “the effect of coopetition on firms,” “the impact of coopetition on the supply chain” and “determinants of coopetition” (Meena et al. , 2022).…”
Section: Foundational Literaturementioning
confidence: 99%